Mathematical reasoning of junior high school students in solving algebraic multiplication: Viewed from personality type - Sitanggang, Damra Ali; Prabawanto, Sufyani (Universitas Islam Negeri Raden Intan Lampung, 2025)
Mathematical reasoning is an important skill for students in thinking critically and solving complex math problems, but this ability is still low, especially in algebraic operations. This study aims to describe the mathematical reasoning ability of junior high school students in solving algebraic multiplication based on personality type. This qualitative research uses a case study with 34 seventh-grade students of public junior high schools. The research instruments include the personality type scale and the mathematical reasoning test. Data analysis includes data reduction, data presentation, and conclusion drawing. The results showed 28.57% of extroverted students had high reasoning, 50% were moderate, and 21.43% were low. Meanwhile, 30% of introverted students have high reasoning, 45% moderate, and 25% low. There are differences in mathematical reasoning characteristics between extroverted and introverted students. This finding has implications for the need for adaptive learning strategies tailored to students' personality types in solving simple and complex mathematical problems.